2008
DOI: 10.1007/s11136-008-9426-2
|View full text |Cite
|
Sign up to set email alerts
|

The relative contributions of race/ethnicity, socioeconomic status, health, and social relationships to life satisfaction in the United States

Abstract: Purpose To evaluate racial/ethnic disparities in life satisfaction and the relative contributions of socioeconomic status (SES; education, income, employment status, wealth), health, and social relationships (social ties, emotional support) to well-being within and across racial/ethnic groups. Methods In two cross-sectional, representative samples of U.S. adults (the 2001 National Health Interview Survey and the 2007 Behavioral Risk Factor Surveillance System; combined n > 350,000), we compared life satisfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
129
4
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(150 citation statements)
references
References 37 publications
13
129
4
4
Order By: Relevance
“…To start with, we found that better physical health (in terms of fewer chronic diseases, better subjective health status, and smaller subjective decline in health) was related to greater physical and psychological well-being. This confirms the role of physical health as a key predictor of well-being in old age [2,[4][5][6][7] .…”
Section: Discussionsupporting
confidence: 78%
“…To start with, we found that better physical health (in terms of fewer chronic diseases, better subjective health status, and smaller subjective decline in health) was related to greater physical and psychological well-being. This confirms the role of physical health as a key predictor of well-being in old age [2,[4][5][6][7] .…”
Section: Discussionsupporting
confidence: 78%
“…In line with previous studies, health status has been associated with happiness (Abbott & Wallace, 2012;Angner, Ghandhi, Purvis, Amante, & Allison, 2013;Padela & Heisler, 2010;Sabatini, 2014;Zajacova & Dowd, 2014) and life satisfaction (Barger, Donoho, & Wayment, 2009;Dubrovina, Siwiec, & Ornowski, 2012;Kim & Sok, 2012;Liang & Lu, 2014). Good health is associated with greater well-being, while setbacks in health have negative effects on subjective well-being.…”
Section: Discussionsupporting
confidence: 84%
“…Acting in a forcing way implies a lack of consideration of other parties' wishes, views and interests and therefore puts pressure on the interpersonal relationship (Dijkstra, De Dreu, Evers, & Van Dierendonck, 2009). This is important because previous studies have consistently shown that good and close relationships with other people are essential for self-reported health (Melchior, Berkman, Niedhammer, Chea, & Goldberg, 2003) and well-being (Baumeister, 1995), and a major source of life satisfaction (Barger, Donoho, & Wayment, 2009) and happiness (Schulz, 1995).…”
Section: Locus Of Controlmentioning
confidence: 99%